How a charismatic leader drives strategic results: Case of Górnik Zabrze football club (Economic and Political Thought, 2017)
On the basis of the entrepreneurial strategy school and leadership theorywe draw the conclusion that firms managed by strong charismatic leadersexclusively responsible for the strategy formulation have higher volatilityof results than firms with a planned and more predicable formal, corporateapproach to strategy formulation. It is so because a strong charismatic leadermay have a clear and solid vision, however he might be wrong and his visioncould result in a significant failure. As a charismatic leader has a stronginfluence on all stakeholders his decisions are usually unquestioned and hispower and his decisions affect the major dependent variable – organisationalperformance. Furthermore, we argue that the entrepreneurial schoolis usually employed in the early stages of a firm’s life cycle. As the firmmatures the role of entrepreneurial visionary strategies scales down leavingthe place for a more formalised planning process. However, in some cases anentrepreneurial visionary strategist is necessary even at the mature stages ofthe organisation life-cycle when the company is a in difficult, turbulent positionas well as in a fierce competitive environment. The entrepreneurial strategicapproach is the most suitable for some types of organisations where otherapproaches would not be so successful. Our findings indicate that a singlecharismatic leader’s strategic management could result in a terrific success orin a terrible failure. However, the entrepreneurial strategic approach shouldnot be mixed with the formal planned approach of strategic management.These two perspectives at least in some type of organisations are mutuallyexclusive because of different fundamental assumptions. While in separationthey could be successful, together they result in a failure.